MANAJEMEN KELAS DALAM MENINGKATKAN EFEKTIVITAS PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA PESERTA DIDIK SEKOLAH DASAR - Marwiyah, St; Alauddin, Alauddin (Institut Agama Islam Negeri (IAIN) Palopo, 2023)
This study explores instructional effectiveness of Islamic education in primary education level. This study aims at identifying class management and the effectiveness of Islamic education instructions, and finding out correlation between the class management and its effectiveness of Islamic education learning. The research applies quantitative research method dealing with correlative ex-post facto. 79 samples in State Primary School Number 12 Langkanae, from 99 of the total population were selected for data collection. Data collection stage deployed observation and questionnaires. The data were subsequently analysed using descriptive statistics and inferential statistics. This study found that there was a significant correlation between class management and Islamic education learning. The result of descriptive statistic analysis revealed that 89,88% (71 students) gave positive responses to the class management and 64,56 (51 students) categorized the Islamic education learning as very good. Furthermore, the analysis of the simple linear correlational test revealed that the class management and the effectiveness of Islamic education learning had a significant correlation, identified from the result of quantification value (0,896) that theoretically indicates that the two variables correlate significantly